Paediatric Day Care Inguinal Hernia Surgery in a General Hospital: A Prospective Study on Change in Practice - Shah, JN; Subedi, N (Journal of Nepal Paediatric Society, 2010)
Introduction: This prospective study was undertaken to observe the prospects of daycare inguinal hernia surgery in general hospital setup in a developing country like Nepal and to assess the advantages, acceptability and safety of this approach. Methodology: The study was carried out prospectively for one year from March 2009- Feb 2010. Before surgery, children were examined in surgical referral clinic (SRC). Parents were given verbal and written instructions for pre-operative fasting. Operations were carried out under intravenous anesthesia without intubation by experienced consultant general surgeon or by registrar under supervision. Children were observed in recovery area till conscious. Once awake, the children were handed over to parents for further observation till fully conscious and could tolerate liquid. Oral Paracetamol and homecare instructions were given to parents. Appointment slip was given for follow up visit in SRC within 3-5 days. Results: There were 90 children, male 81 (89%), age 2 months to 13 years. Right inguinal hernias were 62 (70%). There were no major complications, mortality or readmission. Saving in terms of less disruption of routine work at home and office was more appreciated by parents. Conclusion: We conclude that day care inguinal hernia surgery in children in our setup is safe, economic well accepted by child and parent's both. Key words: Children; Day case hernia surgery; Paediatric inguinal hernia DOI: 10.3126/jnps.v30i3.3913 J Nep Paedtr Soc 2010;30(3):128-131